Mutation of flgM attenuates virulence of Salmonella typhimurium, and mutation of fliA represses the attenuated phenotype. - Schmitt, C K (1994)
Salmonella typhimurium ST39 exhibits reduced virulence in mice and decreased survival in mouse macrophages compared with the parent strain SL3201. Strain ST39 is nonmotile, carries an indeterminate deletion in and near the flgB operon, and is defective in the mviS (mouse virulence Salmonella) locus. In flagellum-defective strains, the flgM gene product of S. typhimurium negatively regulates flagellar genes by inhibiting the activity of FliA, the flagellin-specific sigma factor. In this study, flgM of wild-type S. typhimurium LT2 was found to complement the mviS defect in ST39 for virulence in mice and for enhanced survival in macrophages. Transduction of flgM::Tn10dCm into the parent strain SL3201 resulted in attenuation of mouse virulence and decreased survival in macrophages. However, a flgM-fliA double mutant was fully virulent in mice and survived in macrophages at wild-type levels. Thus, the absolute level of FliA activity appears to affect the virulence of S. typhimurium SL3201 in mice. DNA hybridization studies showed that flgM-related sequences were present in species other than Salmonella typhimurium and that sequences related to that of fliA were common among members of the family Enterobacteriaceae. Our results demonstrate that flgM and fliA, two genes previously shown to regulate flagellar operons, are also involved in the regulation of expression of virulence of S. typhimurium and that this system may not be unique to the genus Salmonella.